Perlindungan Hukum Terhadap Hak Pekerja Kontrak dalam Pemutusan Hubungan Kerja - Hasan, Fuad; Abadi, Suwarno (Universitas Muhammadiyah Ponorogo, 2025)
In Indonesia, the legal protection of workers includes two basic aspects, namely protection from the power of the employer and protection from government action. Legal protection from the power of the employer is implemented if the regulations on labor are implemented by all parties. The purpose of providing legal protection to workers is to create good working relationships and ensure that the rights of workers are implemented and can be fully received in accordance with applicable regulations and labour agreements. The research method used normative juridical research with a statutory approach and conceptual approach. Basically, this employment agreement contains the rights and obligations of the parties, in this case employers and employees. In labor relations, legal protection aims to avoid the arbitrariness of one of the parties. Factors affecting legal protection of workers' rights due to termination of employment include the fact that there are still many business actors who do not carry out their obligations to provide rights to workers in accordance with applicable regulations. Protection related to the rights of workers affected by termination of employment has been regulated in Law Number 6 Year 2023, namely the fulfillment of workers' rights consisting of severance pay, long service pay, and compensation pay that should be received in accordance with the length of service in the company concerned.